PENERAPAN PROSEDUR PEMBUATAN E-KTP BERDASAR PERMENDAGRI NOMOR 7 TAHUN 2019 (Studi Laman Gratis Kabeh di Kecamatan Cilongok, Banyumas) - Ismailia Sisca Widowati; Maesaroh Maesaroh; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Number of residents who haven’t recorded E-KTP in Cilongok shows the highest in Banyumas being the research background. Making E-KTP online is regulated in Permendagri No. 7 of 2019 realized through Gratis Kabeh website. This study analyzes application of procedure for making an E-KTP based on Permendagri Number 7 of 2019 (Gratis Kabeh Websites in Cilongok, Banyumas) and the support or obstacle factors. This research method is descriptive qualitative through interviews and documentation. The theory used was put forward by George C. Edward III. The procedures for making E-KTP through the Gratis Kabeh website in Cilongok are mostly in accordance with Permendagri No. 7 of 2019, but it hasn’t yet been completed with the stages of registering account and affixing e-signature. The supporting variable is active communication through outreach and dissemination of information; availability of complete facilities; and there was no objection from any group; there’s good distribution of responsibilities and coordination between policy implementers. Low quality of village administrator and unavailability of SOP’s are the obstacle factors. The preparation of guidebooks, videos, special programs that substitutes for SOP’s and the provision of periodic training for village admins are the suggestions that the researchers put forward in this study.